The NINDS-Canadian stroke network vascular cognitive impairment neuropsychology protocols in Chinese. Issue 5 (18th December 2012) - Wong, Adrian; Xiong, Yun-yun; Wang, Defeng; Lin, Shi; Chu, Winnie W C; Kwan, Pauline W K; Nyenhuis, David; Black, Sandra E; Wong, Ka Sing Lawrence; Mok, Vincent
Abstract : Background and purpose: Vascular cognitive impairment (VCI) affects up to half of stroke survivors and predicts poor outcomes. Valid and reliable assessement for VCI is lacking, especially for the Chinese population. In 2005, the National Institute of Neurological Disorders and Stroke and Canadian Stroke Network (NINDS-CSN) Harmonisation workshop proposed a set of three neuropsychology protocols for VCI evaluation. This paper is to introduce the protocol design and to report the psychometric properties of the Chinese NINDS-CSN VCI protocols. Methods: Fifty patients with mild stroke (mean National Institute of Health Stroke Scale 2.2 (SD=3.2)) and 50 controls were recruited. The NINDS-CSN VCI protocols were adapted into Chinese. We assessed protocols' (1) external validity, defined by how well the protocol summary scores differentiated patients from controls using receiver operating characteristics (ROC) curve analysis; (2) concurrent validity, by correlations with functional measures including Stroke Impact Scale memory score and Chinese Disability Assessment for Dementia; (3) internal consistency; and (4) ease of administration. Results: All three protocols differentiated patients from controls (area under ROC for the three protocols between 0.77 to 0.79, p<0.001), and significantly correlated with the functional measures (Pearson r ranged from 0.37 to 0.51). A cut-off of 19/20 on MMSE identified only one-tenth of patients classified as impaired on the 5-min protocol. Cronbach's α across the four cognitive domains of the 60-min protocol was 0.78 for all subjects and 0.76 for stroke patients. Conclusions: The Chinese NINDS-CSN VCI protocols are valid and reliable for cognitive assessment in Chinese patients with mild stroke.